Application of 3D Printing in Pharmaceutical Sciences, and Evaluation of Administration Routes for Drug-Loaded Composites - Mohamad Khatami; Ali Doniavi; Saeideh Allahyari; Mahsa Feizollahi; Amir Musa Abazari; Mohamad Fotouhi (Tabriz University of Medical Sciences, 2023)
3D printing is a novel approach in the pharmaceutical field, but its usage has not been fully established. This method can promote drug therapy and overcome some traditional treatment challenges in different ways that are discussed in this paper. "One-size-fits-all", Large-scale production, and less patient and physician acceptability are some limitations that we will encounter in traditional therapy. Three-dimensional printing of pharmaceutical products is a versatile technology that needs specific attention. Droplet-based, extrusion-based, and laser-assisted 3D printers are three main techniques that can be used in this field. The limitations and advantages of this method have been discussed, highlighting potential innovative pathways towards the possibility of drug carriers' usage in ink formulas. The administration pathway of drug-loaded composites is another critical issue in drug treatment strategies that have been discussed here. Oral drug delivery as a convenient method of systemic drug administration with significant patient preference is introduced as the most prevalent pathway that has been studied about 3D printed medicines. Finally, essential ethics and future directions of 3D printing in the pharmaceutical and healthcare industries are outlined.